Preliminary Results of Archaeological Investigations in the Bache Peninsula Region, Ellesmere Island, N.W.T. - Schledermann, Peter (ARCTIC, 1978)
. The preliminary results pertaining to the various cultural stages of the Arctic Small Tool Tradition are presented with special emphasis on 1) the earliest appearance of the A.S.T. tradition, 2) pre-Dorset and transitional pre-Dorset/Dorset developments, and 3) the Late Dorset culture stage. The Thule culture continuum is discussed with particular reference to the earliest stages - 1) Nugdlit, and 2) Ruin Island, with its associated Norse cultural elements.